Exploration of chlorophyll fluorescence characteristics gene regulatory in rice (Oryza sativa L.): a genome-wide association study - Liu, Sicheng; Xiong, Zhuang; Zhang, Zuolin; Wei, Youbo; Xiong, Dongliang; Wang, Fei; Huang, Jianliang (Frontiers in Plant Science, 2023)
Chlorophyll content and fluorescence parameters are crucial indicators to evaluate the light use efficiency in rice; however, the correlations among these parameters and the underlying genetic mechanisms remain poorly understood. Here, to clarify these issues, we conducted a genome-wide association study (GWAS) on 225 rice accessions. In the phenotypic and Mendelian randomization (MR) analysis, a weak negative correlation was observed between the chlorophyll content and actual quantum yield of photosystem II (Φ 𝐼𝐼 ). The phenotypic diversity observed in SPAD, 𝑁𝑃𝑄 𝑡 , Φ 𝑁𝑃𝑄 , and 𝐹 𝑣 𝐹 𝑚 ⁄ among accessions was affected by genetic background. Furthermore, the GWAS identified 78 SNPs and 17 candidate genes significantly associated with SPAD, 𝑁𝑃𝑄 𝑡 , Φ 𝐼𝐼 , Φ 𝑁𝑃𝑄 , 𝑞 𝐿 and 𝑞 𝑃 . Combining GWAS on 225 rice accessions with transcriptome analysis of two varieties exhibiting distinct fluorescence characteristics revealed two potential candidate genes (Os03g0583000 from Φ 𝐼𝐼 & 𝑞 𝑃 traits and Os06g0587200 from 𝑁𝑃𝑄 𝑡 trait), which are respectively associated with peroxisomes, and protein kinase catalytic domains might involve in regulating the chlorophyll content and chlorophyll fluorescence. Transcriptome analysis combined with GWAS of two varieties with different fluorescence characteristics suggested that two candidate genes (Os03g0583000 and Os06g0587200), which are respectively associated with peroxisomes and protein kinase catalytic domains, are involved in regulating the chlorophyll content and fluorescence. This study provides novel insights into the correlation among chlorophyll content and fluorescence parameters and the genetic mechanisms in rice, and offers valuable information for the breeding of rice with enhanced photosynthetic efficiency.